Pengaruh Earning dan Cash Flow Operation terhadap Arus Kas Masa Depan dengan Piutang sebagai Variabel Moderating pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2019-2023 - Chairunisah, Liza; Rangkuti, Lusi Elviani; Lubis, Farida Khairani (Universitas Pahlawan Tuanku Tambusai, 2025)
The objectives of this study are to examine the effects of earnings and cash flow from operations on future cash flows, considering accounts receivable as a moderating variable in these relationships, both partially and simultaneously. The objects of this study are manufacturing companies listed on the Indonesia Stock Exchange during the period from 2019 to 2023. This research employs a quantitative methodology utilizing secondary data. The sampling method used was purposive sampling, resulting in 33 companies from a total population of 48 companies. The data analysis utilized included hypothesis testing, multiple linear regression, classical assumption testing, and descriptive statistical analysis, using EViews software version 12. The study's results demonstrate that the revenue variable exerts a positive and considerable influence on future cash flow. The operating cash flow variable exerts a positive and considerable influence on future cash flow. Consequently, operating profit and cash flow exert a positive and substantial influence on future cash flow. The financing variable does not exert a positive and significant moderating influence on the link between operating profit and future cash flow.